ATMOS/ATLAS-3 Observations of Long-Lived Tracers and Descent in the Antarctic Vortex in November 1994 - Abrams, M. C.; Manney, G. L.; Gunson, M. R.; Abbas, M. M.; Chang, A. Y.; Goldman, A.; Irion, F. W.; Michelsen, H. A.; Newchurch, M. J.; Rinsland, C. P.; Slawitch, R. J.; Stiller, G. P.; et al. (2004)
.Descent rates for atmospheric inferred from ATMOS (Atmospheric Trace Molecule Spectroscopy)tracer observations agree well with theoretical estimates obtained using radiative heating calculations.